The Effect Of The Level Of Implementation Of The Accounting Recording System, The Level Of Accounting Understanding And The Readiness Level Of Msme Actors On The Implementation Of SAK EMKM In MSMEs In Labuhanbatu Regency - Nur Tri Utami Hasibuan; Mulya Rafika; Bhakti Helvi Rambe (UNIVED Press, 2024)
This study utilized a quantitative descriptive approach. The main data for the study was obtained through the distribution of questionnaires and observations. Respondent data were taken from the Labuhanbatu Regency Cooperative and SME Office totaling 100 MSMEs using the Slovin formula. The RSquare (R2) value is 0.234. This proves that the application of the level of use of the accounting recording system (X1), the level of accounting understanding (X2), and the level of readiness of MSME actors (X3) affect SAK EMKM (Y). Outside the variables studied, there are additional elements that account for 76.6% of the total.